The association between spike technique and injuries in competitive volleyball players—a pilot study - Tilp, M.; Pusch, C.; Medeiros, A. I. A.; Wieland, B.; Prosch, Y.; Zentgraf, K.; Kneuhbuhl, I.; Giatsis, G. (Frontiers in Sports and Active Living, 2026)
Background: Different spike techniques in volleyball may vary in performance and shoulder loading, potentially influencing injury risk. However, no previous study has systematically examined the association between spike technique and shoulder injuries in competitive volleyball players. Methods: An online questionnaire was distributed via coaches to competitive volleyball players from Austria, Brazil, Germany, Greece, Portugal, and the USA between December 2024 and February 2025. The survey collected demographic data, spike technique (bow & arrow or circular), self-reported shoulder injuries or symptoms, and related treatments. Coaches classified players` spike techniques based on provided descriptions. Group differences were analyzed using Chi-square tests (p < 0.05). Results: A total of 175 players (90 females, 85 males; mean age 24.3 ± 9.4 years) participated in the study. The bow & arrow technique was most common (71.4%), followed by circular (25.7%). Overall, 32% of the players reported shoulder injuries and 44.7% reported shoulder symptoms. No significant differences in injury or symptom frequency were found between techniques, either overall or within genders (p > 0.05). In females, the circular technique showed lower injury (18.2% vs. 31.2%) and symptom (36.4% vs. 51.6%) rates descriptively compared to bow & arrow, but without statistical significance. Males showed very similar rates for the techniques (injury: 39.1% vs. 34.4%; symptoms: 39.1% vs. 42.6%). Conclusion: The present data do not demonstrate a clear advantage of either spike technique with respect to shoulder injuries or symptoms. Gender-specific trends towards a greater injury risk for women using bow & arrow technique warrant further investigations. Future studies should increase sample size, include a broader range of competitive levels, and also integrate objective biomechanical and medical assessments.